Exploring Attachment Patterns in Patients With Comorbid Borderline Personality and Substance Use Disorders. Issue 11 (November 2015) - Schindler, Andreas; Sack, Peter-Michael
Abstract : Abstract: Studies exploring attachment patterns in samples of patients with borderline personality disorder (BPD) report a combination of preoccupied and fearful-avoidant patterns. This has been interpreted as reflecting the approach-avoidance dilemma of BPD. Comorbid substance use disorders (SUD) have not been considered in these studies, despite the high proportions of SUD among BPD patients and despite the more avoidant attachment in SUD samples. This cross-sectional, naturalistic study explores attachment patterns in a sample of comorbid (BPD and SUD) patients, comparing them to two samples of patients with either SUD or BPD only. Within-group comparisons replicated findings of both preoccupied and fearful-avoidant attachment in BPD and comorbid groups. But between-group comparisons showed that comorbid patients were significantly less preoccupied ( p = 0.018) and more dismissing-avoidant ( p = 0.030). Although both groups were similar in several psychiatric measures, attachment patterns of the comorbid group were more similar to substance abusers than to borderline patients.